IDENTIFICATION OF SEA LEVEL RISE BASED ON TIDAL DATA USING THE LEAST SQUARE METHOD - Anjarwati, Retno; Danial, Mochammad Meddy; Lestari, Arfena Deah; Meirany, Jasisca; Supriyadi, Asep (Fakultas Teknik Universitas Tanjungpura, 2023)
Flood occurs when water overflows its banks due to inadequate channel capacity. Flooding typically results from too much precipitation, which prevents the channel from handling the water flow and results in a deluge. Pontianak City frequently faces severe and protracted flooding when it rains. Both high rainfall and rising sea levels, which impact the Kapuas River, might result in flooding. This argument states that this study was done to anticipate sea level rise for the next six years, which will impact Pontianak City's water flow height using tidal data from Pontianak's Climatology Maritime Station from 2016 to 2021. The average rate of sea level rise, calculated using the least squares approach, is 1.579 cm/year. With an increase rate of 0.017 cm/year, the average sea level rise forecast for the Kapuas River for the next six years is 1.789 cm. It will be necessary to reduce floods in the future to avoid the effects of water flow.